Social Conditions and Cross-National Imprisonment Rates: using Set-Theoretic Methods for Theory Testing and Identifying Deviant Cases - Miethe, Terance D. (Journal of contemporary criminal justice, 2017)
Macro-level theories of punishment suggest that particular social conditions explain national imprisonment rates over place and time. Important causal factors underlying these theories include a country’s level of development, criminality, socioeconomic inequality, and political volatility. Based on a sample of 166 nations and set-theoretical methods, the present study uses the formal logic standards of necessity and sufficiency to evaluate the empirical merits of these widely assumed causal relations. After summarizing the confirmatory evidence and patterns of exceptional cases, results are discussed in terms of their implications for refining current macro-level theories of punishment and future testing of them through the conjunctive analysis of set-theoretic relations.